Correlation between iPTH levels on the first postoperative day after total thyroidectomy and permanent hypoparathyroidism: our experience - Canu Gian Luigi; Medas Fabio; Longheu Alessandro; Boi Francesco; Docimo Giovanni; Erdas Enrico; Calò Pietro Giorgio (Open Medicine, 2019)
Permanent hypoparathyroidism is the most common long-term complication after thyroidectomy. We evaluated whether iPTH concentrations on the first postoperative day may be a good predictor of this complication.